2002
DOI: 10.1108/14601060210451180
|View full text |Cite
|
Sign up to set email alerts
|

Open or closed strategy in developing new products? A case study of industrial NPD in SMEs

Abstract: This case study reports the quality of industrial new product development in five small-to medium-sized enterprises (SMEs) in the Finnish metal industry. The findings indicate that SMEs tend to lack a long run perspective; that the role of new products in business strategy calls for clarity and that the whole goal setting as to future new product efforts is limited. The fit between market requirements and firms' own resources is managed due to the flexibility SMEs have and by relying on an in-house knowledge b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 28 publications
4
20
0
Order By: Relevance
“…Belotti and Tunälv (1999) put forward that innovation is rarely strategic in small companies. Lindman (2002) supports this and finds that reactive behavior to innovation is more common than proactive. A high external uncertainty makes long-term strategies less useful, and short-term returns more favorable than longterm returns in innovation (Mazzarol and Reboud, 2005;Westhead and Storey, 1996).…”
Section: Small Companies and Product Innovationsupporting
confidence: 59%
See 1 more Smart Citation
“…Belotti and Tunälv (1999) put forward that innovation is rarely strategic in small companies. Lindman (2002) supports this and finds that reactive behavior to innovation is more common than proactive. A high external uncertainty makes long-term strategies less useful, and short-term returns more favorable than longterm returns in innovation (Mazzarol and Reboud, 2005;Westhead and Storey, 1996).…”
Section: Small Companies and Product Innovationsupporting
confidence: 59%
“…Freel (2000) found frequent use of vertical networking with suppliers and customers. Horizontal networking has been found to be less frequent in innovation (van de Vrande et al, 2009), andLindman (2002) and Mazzarol and Reboud (2005) have found that a majority of small companies develop their innovations alone without support from horizontal actors. Regarding the informality and structures of small companies' product innovation, Bolinao (2009) proposes that small companies seldom have the resources or infrastructure to perform product innovation in a formal and strategic way.…”
Section: Small Companies and Resource Scarcitymentioning
confidence: 99%
“…This is particularly relevant in the new product development (NPD) and commercialisation processes in which SMEs need to make the best use of available resources and avoid the high risk of short production runs in response to immediate customer needs (Lindman, 2002).…”
Section: A Resource-based View (Rbv) Of Organisational Factors Influementioning
confidence: 99%
“…An SME owner-manager's ability to identify and exploit potential opportunities is an important determinant of their success in commercialising an innovation (Kirzner, 1997). However, this success is often based on informal and intuitive thinking, due to a lack of information and capacity to assess innovation risks and returns (Lindman, 2002;Duhamel et al, 2014). SMEs also frequently lack a systematic approach to commercialisation, reducing their chance of success (Wheelen and Hunger, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The major risk of such strategies is inability to identify and pursue any business opportunity outside the present product scope (Tapio Lindman, 2002). Successful new product development requires strong interactions with customers through sales, marketing and product design activities in order to clearly understand changes in customer needs (Handfield et al, 1999).…”
Section: Introductionmentioning
confidence: 99%